2022
DOI: 10.3233/shti220717
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Wound Type Classification with Convolutional Neural Networks

Abstract: Chronic wounds are ulcerations of the skin that fail to heal because of an underlying condition such as diabetes mellitus or venous insufficiency. The timely identification of this condition is crucial for healing. However, this identification requires expert knowledge unavailable in some care situations. Here, artificial intelligence technology may support clinicians. In this study, we explore the performance of a deep convolutional neural network to classify diabetic foot and venous leg ulcers using wound im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… 14 In this study, noninvasive biotechnological devices were used to obtain measurement results on skin parameters, which were used to train the AI. In the study by Malihi et al., 15 neural networks were used to classify wound types, and in the Gibstein et al. study, 16 neural networks were applied to assess surgical outcomes after face lift surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 In this study, noninvasive biotechnological devices were used to obtain measurement results on skin parameters, which were used to train the AI. In the study by Malihi et al., 15 neural networks were used to classify wound types, and in the Gibstein et al. study, 16 neural networks were applied to assess surgical outcomes after face lift surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A possible more objective system for skin type classification was applied by Seo et al 14 In this study, noninvasive biotechnological devices were used to obtain measurement results on skin parameters, which were used to train the AI. In the study by Malihi et al, 15 neural networks were used to classify wound types, and in the Gibstein et al…”
Section: F I G U R Ementioning
confidence: 99%
“…They trained a CNN algorithm model on 863 cropped wound images and evaluated its performance using a test set. The study reported an F1-score of 0.85 for cropped test images and an F1-score of 0.70 for complete images in the trained deep CNN model [33]. Furthermore, CNNs have demonstrated utility in segmenting wounds in microscopic imaging.…”
Section: Related Workmentioning
confidence: 97%
“…Similarly, in Ref. [21], the Xception model with pre-trained weights was employed to classify diabetic and venous ulcers. The model was evaluated on a private wound image dataset (909 wound images), and 83% and 67% accuracy were achieved for cropped and full wound images, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%